Implementation Of Quality Control Analysis Techniques On A Blood Product As A Case-Study - Al-Juboori, Salloom A. (European Scientific Journal, ESJ, 2016)
Save and high blood quality is an indispensable need for every patient. Providing adequate blood products for the patients is the aim of the hospital KH(deliberately didn't mention the name of hospital) that’s why they introduced the quality management department to be sure of serving the hospital needs by operating under the 10 quality system essentials to be in control of all of its processes in a cost-effective way. KH is an accredited member with the American Association of Blood Banks (AABB) since 1989, and participating of the Collage of American Pathologists (CAP) since 1994 in order to make sure of being developed in their services. In this work the a comprehensive field study was implemented to analyze the quality of the system in order to know its weaknesses and try to improve it, and to assure that safety is applied according to specific standards to provide safety environment to the employees, customers and visitors in all areas of the blood bank. The main causes or errors that lead to discarding blood units are studied. As a result of this work suggested solutions were obtained to reduce causes or errors. Safety aspects were analyzed and improved; issues related to quality management such as filing system of documents tracking information flow between blood bank departments were improved.